When Your Refrigerator Orders Groceries Online and Your Car Dials 911 After an Accident: Do We Really Need New Law for the World of Smart Goods? - Jean Braucher (Washington University Journal of Law & Policy, 2002)
In this Essay, I argue that the law of goods does not need change in many of its elements despite current technological change. Furthermore, I argue that it makes sense to treat copies of freestanding software as goods even if they are in electronic files. One body of law should govern transactions in hardware and software, including refrigerators, cars, personal computers and their operating systems, manufacturing and medical equipment, as well as freestanding software itself. These products are all properly classified as goods. For these products, Article 2 of the Uniform Commercial Code (U.C.C.) successfully addresses issues of contract formation, warranties, performance standards, and damages.
Keywords: Digital technology; Electronic commerce; E-commerce; Product quality; Software; United States